Pengaruh Sarana dan Prasarana Sekolah Terhadap Peningkatan Motivasi Belajar Siswa UPT SPF SD Negeri 104202 Bandar Setia Kecamatan Percut Sei Tuan Kabupaten Deli Serdang T.A 2023/2024 - Anggraini, Nuri; Herdyana, Thessa; Ramadhani, Mastari (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This research employed a descriptive qualitative method, aiming to reveal the real conditions of a specific social phenomenon. The study focused on examining the influence of school facilities and infrastructure on enhancing learning motivation among fifth-grade students at UPT SPF SD Negeri 104202 Bandar Setia, Percut Sei Tuan, Deli Serdang Regency. The research involved 30 students as participants and was conducted over six meetings. The analysis considered the availability of educational facilities such as classrooms, sports areas, places of worship, libraries, laboratories, and other essential resources, including the use of information and communication technology, in supporting the learning process. Hypothesis testing revealed that the correlation coefficient (r) from the calculations (0.484) exceeded the critical value from the r distribution table (0.361), with a significance level of 5%. This indicates a positive and significant effect of school facilities and infrastructure on increasing student learning motivation.